Anatomi Akad Asuransi Syariah dalam Perspektif Fatwa Dewan Syariah Nasional (Studi Kasus Produk Mitra Iqra AJB Bumiputera Cabang Syariah Surakarta) - Husen, Fathurrohman (SHAHIH: Journal of Islamicate Multidisciplinary, 2021)
Standard contracts in sharia insurance products must be adjusted to the fatwa of the Sharia Council of the Indonesian Ulema Council (DSN-MUI). The fatwa becomes a reference for determining the condition of insurance institutions in Indonesia. This study aims to analyze the insurance contract on the Mitra Iqra Plus product at AJB Bumiputera 1912, the Surakarta Sharia Branch office against the conformity of sharia principles based on the DSN-MUI Fatwa. The method used is a descriptive qualitative approach and juridical-normative analysis. The findings of interview, observation, and documentation data show that the standard contract applied in the policy is in accordance with sharia principles. Explanation of the flow and process of the contract is conveyed in a sales aid designed to maintain the principle of transparency. The policy analysis shows that there are articles related to the understanding between the parties regarding the three contracts. First, the tabarru 'contract is used to pay members' claims. Second, the mudharabah contract is used for managing investment funds. Third, the wakalah bil ujrah-muqayyadah contract is used for the power of management of the entire fund by the insurance company. The principle of taradhin (willingness) is carried out by giving a tempo to understand the policy before signing it. In conclusion, it is necessary to specifically mention the terms of the mudharabah musytarakah contract in the policy. The basis for the provisions is fatwa Number 51 / DSN-MUI / III / 2006 which regulates the management of investment funds, as a form of clarity that the investment capital that is managed comes from funds owned by the company and owned by members.